Evolution and Innovations of the National Neonatal and High Risk Screening Program in Costa Rica - de Céspedes, Carlos (2004)
We present the evolution, organization and results of the National Neonatal and High Risk Screening Program in Costa Rica (PNT). This program has been working uninterruptedly for more than fourteen years. Costa Rica currently has a literacy rate of 95%. To August 2004 the rate of infant mortality was 9.74 per 1000 births and to 2003, life expectancy was 76.3 years for men and 81.1 years for women. The control of infectious and parasitic diseases, as well as of severe malnutrition, has given room to a prevalence of chronic diseases with a pathology profile similar to that of a developed country. The clinical observation, mainly starting from early 70s, of a growing number of patients with mental retardation and other disabilities caused by congenital hypothyroidism and hereditary metabolic diseases that could have been prevented in many cases with an early diagnosis and opportune treatment, led us to the decision to implement a systematically massive neonatal screen- ing for these diseases. The presence of a single Public System of Social Security in Costa Rica, which current- ly includes from primary health care up to the hospitals of tertiary attention, with a single Children’s Hospital for the whole country, as well as communication facilities, are factors that offered, in principle, favorable con- ditions for this effort, even for a developing country. To September 2004, 835,217 children have been screened. There is a coverage of 95.1% of the newborns in the country. Also to this date, 259 children with congenital hypothyroidism, 18 with phenylketonuria, 20 with the maple syrup disease, 30 with congenital adrenal hyper- plasia and 10 with galactosemia have been detected, confirmed and treated, for a total of 337 children that were spared of mental retardation, other disabilities and even death. Massive neonatal screening for organic acidemias recently started in June of 2004. Cystic fibrosis is under a pilot study and the screening for hemoglobinopathies and toxoplasmosis is planned. The Center for Prevention of Disabilities, which started its functions on September 23, 2002, made feasible to integrate neonatal screening, high risk screening and diagnostic confir- mation of the diseases now included in the national screening program as well as those to be added in the future.